THE RISE OF IDEOLOGICAL POLARIZATION IN PAKISTAN: IMPLICATIONS FOR ELECTORAL POLITICS AND DEMOCRATIC STABILITY (Contemporary Journal of Social Science Review, 2025)
The growing intensity of ideological polarization has emerged as one of the most defining features of Pakistan’s contemporary political landscape, reshaping electoral behavior, party competition, and perceptions of democratic legitimacy. This qualitative study explores how ideological divisions—rooted in religion, nationalism, class, and party identity—are influencing political participation and simultaneously challenging democratic stability in Pakistan. Using a phenomenological research design, the study draws on in-depth semi-structured interviews with political activists, youth voters, journalists, and local community leaders across diverse socio-political settings. The thematic analysis reveals that polarization in Pakistan is no longer limited to party loyalties; it now reflects deeply ingrained identity-based worldviews, amplified by digital media echo chambers and emotionally charged political rhetoric. Participants consistently reported that political discussions have become increasingly confrontational, fostering mistrust between groups and reducing the space for dialogue, compromise, and reasoned debate. Findings also show that ideological polarization shapes voting decisions by reinforcing rigid in-group biases, driving symbolic politics over policy-based choices, and escalating support for populist narratives. Moreover, respondents expressed concerns that extreme polarization undermines institutional credibility, weakens social cohesion, and intensifies the potential for democratic backsliding. While polarization energizes political engagement for some, it simultaneously diminishes pluralism and discourages dissent. The study concludes that ideological polarization poses a significant risk to Pakistan’s democratic stability, calling for renewed civic education, media literacy, and cross-party dialogue mechanisms. The research provides a nuanced understanding of polarization’s socio-political consequences and offers a foundation for future studies examining its long-term implications for Pakistan’s political development.